If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(a + -2b + 3a + -2b) = 2(-2 + -3b) Reorder the terms: -5(a + 3a + -2b + -2b) = 2(-2 + -3b) Combine like terms: a + 3a = 4a -5(4a + -2b + -2b) = 2(-2 + -3b) Combine like terms: -2b + -2b = -4b -5(4a + -4b) = 2(-2 + -3b) (4a * -5 + -4b * -5) = 2(-2 + -3b) (-20a + 20b) = 2(-2 + -3b) -20a + 20b = (-2 * 2 + -3b * 2) -20a + 20b = (-4 + -6b) Solving -20a + 20b = -4 + -6b Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-20b' to each side of the equation. -20a + 20b + -20b = -4 + -6b + -20b Combine like terms: 20b + -20b = 0 -20a + 0 = -4 + -6b + -20b -20a = -4 + -6b + -20b Combine like terms: -6b + -20b = -26b -20a = -4 + -26b Divide each side by '-20'. a = 0.2 + 1.3b Simplifying a = 0.2 + 1.3b
| 0=9x+3 | | 3y^2-10y+7=0 | | 9q+15q= | | =.2x^2-2.4x+.2 | | 6(k-3)-5(k+2)= | | =2x^2-4x+9 | | 250+125x+x^2=1250 | | 3*x^2+8*x+4=0 | | 7y^2-34y-5=0 | | 2x+5x-3x+4=3x | | 7y^2+13y-2=0 | | =2x^2+16x-2 | | 4x^2-21x-49=0 | | 4x+5+2x=7x | | 4x-21x-49=0 | | .25(x-8)=6 | | 13-3x=-6x+16 | | 5y-1+5y=4 | | 255=(-2x)(.147-x)(.18-x) | | 2x+3x=32 | | 3x^2-67x=-6x^2-5x-48 | | =-2x^2-28x-96 | | 3x^2-10x+25=0 | | -4m+8=-3m+1 | | .5(x-6)=4 | | X^3-64y^3= | | 4*x^3-12*x^2+10*x-8=0 | | 2a^2+7a-9= | | 5+.25n-1.25n=n | | 32+3x(x-4)=8x-40 | | 5x-13=6x-7 | | x-7.4=-5.8 |